An econometric model for non-timber forest products in the Brazilian Amazon - Brasil, Alexandre Anders (2023)
The objective of this study is to identify the determinants of Non-Timber Forest Products (NTFPs’) supply and demand in the Amazon region. The method applied was an econometric model of supply and demand in a log-linear form. Based on consumer and firm theories as well as studies on the market for extractive products, we developed models of supply and demand for NTFPs. The models were estimated by Ordinary Least Squares (OLS) in the log-log functional form, allowing to obtain the elasticities of the variables that affect the NTFPs supply and demand. The results indicated that during the study period, the behavior of the NTFPs market was stable in terms of the price and the quantities produced. These products displayed low elasticity in relation to price, both on the supply and the demand sides. This indicates that the cultivation of NTFPs (producing species) is a better option than the expansion of extractive activity. We conclude that the modernization of extractive production, the development of the products, and government support for commercialization are essential for the development of sector and the local community.